الدلالات النفسية والاجتماعية للفظ " القيام" في السياقات القرآنية: دراسة وصفية تحليلية - موسى، محمود أحمد،‏ ‏1985-
The research aimed at manifesting the psycho-sociological meanings of the word “Al-qiyam” and its derivatives as in different qur'anic contexts; for its religious and linguistics gravity and value, not to mention its quantifiable worthiness both socially and psychologically; that is because the aforementioned meanings were being perceived as the most flourished linguistics products nowadays, though its application in qur'anic studies is unfortunate as compared to linguistics studies. The research idea emerges while paging a series of books called “ kutubul wuju wannadhair li-alfadhil qur'an” and “kutubu ma'nil qur'an al-mashhur”; as such the research adopts two main methods; thus: Descriptive method which focuses on theoretical aspects and Analytical method is also used to tackle the application part in analyzing the verses in which the word “Al-qiyam” and its derivatives emerged contextually in order to get their exact meanings. so as to extract their inspired meanings psychologically and sociologically as accompanied and conveyed in the text. The result of the research indicates the gigantic and weighty role of the context and confirms its essence in determining the psycho-sociological relevance. The psychological aspects of the context were also noted in the chapters sampled in the study. These aspects involve love, consciousness, fearness, tension as well as confusion and some other words that were mentioned in the psycho-analysis of the study.